Perception of the contamination of the Opamayo river by the population of Pampas Tayacaja-Huancavelica - Alvarez Ticllasuca, Adiel (2022)
This article presents the perceptions of the inhabitants of the district of Pampas Tayacaja on the contamination of the water of the Opamayo River, its effects and its origin. It should be noted that this tributary along its route is polluted by the effects of agriculture, livestock and municipal drains, among others. A common perception is that the quality of the water in the Opamayo River ranges from good to very bad. Most of the people interviewed said that the river water is not clean because there is no proper treatment and that in the dry season the river presents clear water with small stones, and this visually indicates that the water is in the state. mesotrophic. The main source of contamination of the Opamayo River has been identified as the discharge of sewage into the river and the dumping of garbage. Respondents hope that having the sanitation of the Opamayo River have benefits, especially for their descendants, who could enjoy the river with clean water for agricultural use. However, they are skeptical about the role of government institutions in solving the problem